Clinico-pathological study of oesophageal cancer: a 3 years retrospective and 1½ year’s prospective analysis - Suryawanshi, Shrikant S.; Chenkula, Saia; Zohmingthanga, John; Ralte, Zothansanga (International Journal of Research in Medical Sciences, 2021)
Background: In India, oesophageal cancer is second most common cancer among males and fourth most common among females and is associated with certain diets and lifestyle. In India, the age-adjusted incidence rates for oesophageal cancer are the highest in men (25.5) and women (5.5) in Mizoram. Aim of the study was to find the clinical and histopathological findings of oesophageal cancer patients at Civil Hospital, Aizawl. Methods: A descriptive study (3 years retrospective and 1½ years prospective) was conducted at Civil Hospital, Aizawl, Mizoram from July 2013 to December 2014 (1½ years) amongst 104 patients reporting to Civil Hospital, Aizawl for oesophageal cancer. Results: History of progressive dysphagia to solids was most common symptom and observed in 91.3% patients. Histopathological examination of resected esophageal specimen showed 95.7% patients were detected with squamous cell carcinoma, 4.3% patients were detected with no proper malignancy/residual tumor. Conclusion: Squamous-cell carcinoma was the most common type of esophageal cancer occurring in the middle third of the oesophagus with as observed on upper gastrointestinal (GI) endoscopy. More men were affected than female.